5-iodonaphthyl azide labeling of specific membrane proteins via energy transfer from donar chromophores - Meiklejohn, Bruce I., author; Barisas, B. George, advisor (Colorado State University. Libraries, 1991)
The conditions required for activation of 5-iodonaphthyl-1-azide (INA) by energy transfer from donor chromophores have been examined and methods developed for identifying specific plasma membrane proteins proximal to known plasma membrane receptors. INA is hydrophobic and when inserted in the plasma membrane lipid bilayer, can be activated through energy transfer from the donor fluorochrome, eosin isothiocyanate (EITC). The energy transfer efficiency was greatly increased under anaerobic conditions; the triplet lifetime of EITC conjugated to BSA increased from 10 μ sec to approximately 1 msec in solutions treated with glucose oxidase and catalase for 120 min. To determine whether [125I]-INA would specifically label known membrane proteins, a μ-chain specific EITC-derivatized anti-murine IgM antibody was incubated with murine B-lymphocytes treated with 2. 6 x 10-5M [125I]-INA. When B-lymphocytes were irradiated with 40 mW per centimeter 514 nm light from an argon ion laser, the 66 kDa IgM heavy chain was derivatized with INA and identified on autoradiographs of SDSPAGE gels. In similar experiments, 2H3 rat basophilic leukemia cells were incubated with EITC-IgE which bound to the monomeric Fcε receptor. Four [125I]-INA derivatized plasma membrane proteins with molecular weights of 53, 38, 34, and 29 kDa were identified on autoradiographies of SDS-gels. When IgE was crosslinked with mouse anti-rat IgE three additional proteins with molecular weights of 60, 54, and 43 kDa, were labeled with the photoprobe. Under these conditions the receptor was known to be part of large molecular weight aggregates which contain non-receptor proteins. Collectively, these results suggest that INA may be useful in characterizing protein-protein interactions in the plasma membranes of intact cells under physiological conditions.
Covers not scanned
Keywords: Membrane proteins; Energy transfer; Membranes (Biology); Biological transport